Kedaulatan Rakyat di Indonesia: Konsep Yang Dianut Dan Konsekuensinya di Dalam Pembentukan Peraturan Perundang-Undangan - Atma Hajri, Wira; Susanti, Heni; Ardiansyah, Ardiansyah; Nabila, Nabila (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2023)
One of concepts of sovereignty or the highest power adopted by the 1945 Constitution of the Republic of Indonesia is the concept of people's sovereignty. This is found in Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. As a concept that originates from outside, of course this concept receives diverse views from various groups. This is understandable because any concept is definitely not value-free. It is influenced by various factors such as religion, ideology, politics, history, and so on. Besides that, ethnicity as a concept in the life of the state, of course influences other fields, including in the formation of laws and regulations. Therefore, the purpose of this research is to find out the concept of people's wealth which is adhered to by the 1945 Constitution of the Republic of Indonesia. In addition, this research is also intended to develop the concept of ethnicity which is adhered to in the formation of laws and regulations in Indonesia. The result of the research is that the People's Sovereignty adhered to by the 1945 Constitution of the Republic of Indonesia is limited by the power of God. This is different from the concept of the original version of the people's area. Where the people's choice is absolutely in the hands of the people. This departs from the understanding of a country that is neutral from religion. Meanwhile, the consequence of the concept of ethnicity that is adhered to in the formation of laws and regulations is that each formation of statutory regulations is limited by the provisions of God Almighty. So that deliberations or voting can be carried out when there is no explicit regulation by the provisions of the Law of God Almighty.